(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The crisis is a human phenomenon and part of daily life, which is inherent to the human being that arises at any moment and in sudden times as a result of internal or external conditions that create a kind of threat to the state or the individual and it is imperative to deal with it to reduce its risks and then eliminate it and limit its losses until it has become a feature of life Contemporary, which requires attention and management to adapt to the urgent changes that may occur during the crisis. In times of crisis, the public needs clear information about what is happening, it also needs an explanation of what is happening and a visualization of the course of the crisis, and a clear explanation of what needs to be done. The media in general is the means to provide information, provide explanation, and interpretation, and is also responsible for educating the public about the best behavior in dealing with the crisis. The many bets and repercussions that characterize each crisis? It has been proven that political crises are managed in large part by the media, and this is evident in the influence of the media on the course of events in the Arab arena. Perhaps the most explosive crises are the Syrian scene, where the Syrian crisis formed a media material for all Arab and Western satellite channels that interacted with the crisis Or against it, some of which played a positive role in its interaction with the crisis, and some of them played a negative role through misleading and absenteeism in public opinion. Given the importance of this issue and the great role that the media plays through its satellite channels in political change, we will try to shed light on the role played by satellite channels, especially Al-Jazeera in its management of the Syrian crisis.